KAJIAN PENDAPATAN DAN KEMISKINAN RUMAH TANGGA PEDESAAN MISKIN DI JAWA TENGAH - Suprapti Supardi; Sri Marwanti (Universitas Sebelas Maret, 2004)
Distributing proverty in rural Central Java consist various area of various nature resource potensial with proportion of proverty village is 28.71 prosen. The research aims to analysis income and proverty household in poor rural Central Java with purposive location research. The result of the research shows more than half of household is agriculture household that get bigger income from non agriculture and poor population calssified